PHYSIOCHEMICAL ASSESSMENT OF LANDFILL GENERATED LEACHATES IN LAGOS, NIGERIA - Christopher N Akujieze; Imoukhuede Moses IDEHAI (International Journal of Science and Engineering, 2014)
About 3.5 million tonnes of comingled municipal solid wastes (MSW) are dumped annually into the landfill areas of Lagos in Nigeria with a human population of about 21 million. Upon geo-bio-chemical processes, leachates are produced which are improperly collected and may be introduced to the environment with possible insidious effects on human health. Eight (8) composite leachates samples were collected from four (4) landfills in the megacity and tested for their physiochemical parameters in order to determine their suitability for discharge into agricultural soils and groundwater systems. Geological  site investigation reveal that the landfills except Epe have significant attenuative clayey soil protection above groundwater, and can adsorb and/ or precipitate contaminants/ pollutants within its mass. Using ANOVA, juxtapositions of the Fcalculated with the  Fcritical values revealed a metal sequence of : Hg  > Zn >As >Mn >Ni >K >Pb >Cr>Cd>Fe. Also, total alkalinity> total hardness> total acidity. All the measured  anions had Fcalculated above Fcritical values and were in  the hierarchy : Chloride> sulphate> phosphate>nitrate.. Mean concentrations were in the order  : Fe>Cd>Cr>Pb>K>Ni=Mn>As>Zn>Hg. Fe also posted the highest value for standard deviation. Results of the ratios of the standard deviation to the means were in the sequence: Fe> Zn>K> Ni > Mn>Pb> Cr> Cd> Hg> As. The presence of arsenic above prescribed limits in the Epe leachate is a  major concern because the lithology is sandy, and has a reported depth of about 3m to the unconfined aquifer that adjoins the Epe Lagoon. This  expansive landfill is recommended for closure.